How Long Is a Normal Labor? Contemporary Patterns of Labor and Birth in a Low-Risk Sample of 1,612 Women from Four Nordic Countries - Hildingsson, Ingegerd; Blix, Ellen; Hegaard, Hanne; Huitfeldt, Anette; Ingversen, Karen; Ólafsdóttír, Ólof Ásta; Lindgren, Helena (Birth (Berkeley, Calif.), 2015)
Objective Normal progress of labor is a subject for discussion among professionals. The aim of this study was to assess the duration of labor in women with a planned home birth and spontaneous onset who gave birth at home or in hospital after transfer. Methods This is a population‐based study of home births in four Nordic countries (Denmark, Iceland, Norway, and Sweden). All midwives assisting at a home birth from 2008 to 2013 were asked to provide information about home births using a questionnaire. Results Birth data from 1,612 women, from Denmark (n = 1,170), Norway (n = 263), Sweden (n = 138), and Iceland (n = 41) were included. The total median duration from onset of labor until the birth of the baby was approximately 14 hours for primiparas and 7.25 hours for multiparas. The duration of the different phases varied between countries. Blood loss more than 1,000 mL and perineal ruptures that needed suturing were associated with a longer pushing phase and the latter with country of residence, parity, single status, and the baby's weight. Conclusion In this population of healthy women with a low prevalence of interventions, the total duration of labor was fairly similar to what is described in the literature for multiparas, but longer for primiparas. Although the duration of the phases of labor differed among countries, it was to a minor extent associated with severe outcomes.